EKSPLORASI DIMENSI GOTONG ROYONG DALAM PENGUATAN PROFIL PELAJAR PANCASILA SISWA KELAS VI DI MI SALAMAH - Wangi, Indah Ayu; Fia Alifah Putri (Sindoro: Cendikia Pendidikan, 2025)
This research addresses the important issue of exploring the dimension of mutual cooperation in strengthening the Pancasila Student Profile of sixth grade students at MI Salamah. The implementation of the Pancasila Student Profile Strengthening Project (P5) for students in schools presents its own challenges for educators who play multiple roles amid limitations and constraints related to the students. The main objective of this research is to identify and analyze the implementation of the value of mutual cooperation in the P5 project, including the supporting and inhibiting factors. This study uses a qualitative descriptive approach. Data sources were obtained through interviews with teachers and students, student questionnaires, observation, and documentation. The results of this study indicate that overall, the implementation of the value of mutual cooperation in the P5 project is carried out through various strategies that integrate these values into learning and everyday school life, such as collaborative group discussions, social and caring activities, and student creativity competitions. The supporting factors in implementing the value of mutual cooperation include the teacher’s role as a facilitator to assist students, students’ enthusiasm, and the presence of a "Gelar Karya" (exhibition of student work). Meanwhile, the inhibiting factors are differences in student character, the teacher’s readiness in classroom management, and time limitations in executing the P5 project. In conclusion, the implementation of the value of mutual cooperation in the P5 project for sixth-grade students at MI Salamah follows a sequence aligned with the project’s objectives, consisting of introduction, contextualization, action, reflection, and follow-up